Pengaruh Sarana Dan Prasarana Perpustakaan Terhadap Minat Baca Mahasiswa Semester 2 Program Studi Manajemen Pendidikan Islam Institut Agama Islam Darussalam Blokagung Banyuwangi Tahun Akademik 2018/2019 - Aminulloh, Achmad; Nahdliyah, Amirotun; Imamah, Istianatul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2019)
This study aims to: (1) Determine the facilities and infrastructure of the library of the Islamic Institute of Islam, BlokagungBanyuwangi; (2) Determine the reading interest of semester 2 students in the Islamic Education Management study program at the Darussalam Islamic Institute, BlokagungBanyuwangi; (3) Determine the influence of library facilities and infrastructure on the second-semester students' interest in reading Islamic Management of the Islamic Institute of Religion, BanyuwangiBlokagung. This study uses quantitative descriptive methods with data analysis techniques using simple linear regression analysis techniques. The population of this research is the second-semester students of the Islamic Education Management Study Program of the Darussalam Institute of Religion BanyuwangiBlokagung, amounting to 90. After analyzing the data, it was found that: (1) the facilities and infrastructure of the AsaiSyafa'ah IAIDA BlockagungBanyuwangi are classified as good; (2) reading interest of semester 2 students of IAIDA Blokagung Islamic Education Management study program is quite good; (3) there is an influence of library facilities and infrastructure on the reading interest of semester 2 students in the Management of Islamic Education, Institut Islam Darussalam BlokagungBanyuwangi is 79.9%.